Use and abuse of the inclusion and exclusion criteria in the research project - Luis Alberto Corona Martínez; Mercedes Fonseca Hernàndez (Medisur)
One of the essential methodological aspects of an investigation is the delimitation of the subjects to be studied. This article addresses the current trend towards an excessive and unjustified statement of inclusion and exclusion criteria in all types of research. The idea is defended that an adequate use of the universe and sample categories makes it unnecessary to declare inclusion and exclusion criteria in the methodological design of most of the specialty completion work projects presented by our residents.